Integrating Financial Management into Hotel Restaurant Operations - Murdiani Sukarana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Hotel restaurants face significant challenges in managing food waste, resource allocation, and pricing, which undermine profitability and operational efficiency. This study aims to analyze the role of financial management in menu development and pricing decisions to enhance the performance of hotel restaurants. Employing a library-based research approach, the study reviews secondary data from books, journals, and articles published between 2005 and 2025, using content analysis to identify key themes. The findings reveal that integrating financial principles, such as cost-volume-profit analysis and demand theory, can reduce food waste through strategic menu design and increase revenue with dynamic pricing strategies. However, many hotel restaurants struggle with inadequate financial tools and static pricing models, leading to inefficiencies. The study concludes that adopting robust financial management practices, including menu engineering and flexible pricing, enables managers to optimize resources and align offerings with market demands. These strategies foster sustainable profitability and improved customer satisfaction, offering practical solutions for hotel restaurant managers to address operational challenges effectively.